MANAGERIAL ANALYSIS AS AN INSTRUMENT OF CRISIS MANAGEMENT - V. N. Alferov (Модернизация, инновация, развитие, 2018)
Purpose: the main purpose of this article is to explore the possibility of applying management analysis as a mechanism for anti-crisis management and expanding tools for implementing crisis management in making effective management decisions. To achieve this goal, the following problems are solved in the article: determination of the place and content of management analysis in the system of economic analysis; identification of distinctive features, shortcomings and advantages in the conduct of financial and management analysis; generalization of features of application of methods of the administrative analysis; proposal and assessment of the place and functions of management analysis in the activities of the controlling service within the framework of crisis management in an economic entity.Methods: this article is based on an interdisciplinary approach to the organization of crisis management in relation to the specifics of management accounting and analysis.Results: currently, in the period of the constant appearance of external and internal factors of the crisis, the most important direction of stabilizing the financial situation of business structures is the development and effective use of anti-crisis management. This allows us to protect the vital interests of economic entities, the key element of which is stable activity and economic sustainable development. Ensuring the economic development of economic entities begins with the proper organization of crisis management and the effective use of its tools. One of the tools in conducting anti-crisis management is a financial analysis that has certain characteristics and disadvantages. The use of management analysis along with financial analysis will allow us to assess and prevent the emerging crisis phenomena in advance, stabilize the financial situation, identify factors and reserves for the anti-crisis development and subsequent economic sustainable development of economic entities. Conclusions and Relevance: the materials outlined in the article show the special role and importance of management analysis in the development of anti-crisis management in an economic entity, stabilization of its financial position and enhancement of its efficiency. To manage economic activity, management must investigate and monitor changes that occur not only in the external, but also in the internal environment of the organization. The possibility of using managerial analysis for managing economic activity, studying the results of financial and economic activities and controlling their changes, identifying negative internal factors, determining the advantages and disadvantages in order to ensure the adoption of sound and effective management decisions is analyzed.